A Glimpse of Indian Financial Sector Risk Management Framework (International Journal of Innovative Research in Engineering & Management, 2021)
The latest Credit Derivatives Determination Committee 2021,  established by the top bank Reserve Bank of India (RBI),  outlines the way forward for the credit derivatives market.  Indian derivatives are equities, bonds, commodities and  currencies. The Bombay, the National Stock Exchange and the  Multi Commodity Exchange are accessible. However, the banks'  market for credit derivatives or securitisation is mostly absent.  This is one of the most important components of the developed  economy worldwide. The primary feature of the credit  derivative is that it transfers the risk of the originator to  investors who are ready to accept the risks and be exposed to the  market to diversify their investments. One benefit of bank credit  derivatives is that it lowers deposit dependence as capital and  makes banks more accountable to manage their risk exposure.  Not to add accountability and transparency, because they are  evaluated by credit rating agencies, when it issued the credit  derivatives. Credit derivatives are designed to transfer risk, call  risk, and credit risk. The purpose of this study is to analyse the  possibilities and difficulties of the market in credit derivatives in  India, particularly for banks that are undercapitalized and have  significant problems with their repayment. How this would also  alter the whole market from an investment perspective. This  article also presents the idea of credit derivatives and its many  histories and aspects at their inception. The article is conceptual  in nature and serves to establish a path ahead for future study  when the market peaks. However, RBI issued the previous  circular in 2011 under the heading of "Revised Credit Default  Swap (CDS) Guidelines for Corporate Bonds," which did not  fully explore the market's potential. Almost ten years later, the  current circular on the creation of the committee of 2021 looks  forward to its recovery and reduces the dependence of the banks  on its traditional sources of funding. Only time will tell how far  it was accomplished in the Indian banking industry with so  many difficulties.
Keywords: Credit Derivatives; Credit Default Swap; OTC; Portfolio; RBI